Influence of volatiles (H$_{2}$O and CO$_{2}$) on shoshonite phase equilibria - Vetere, Francesco; Namur, Olivier; Holtz, Francois; Almeev, Renat; Donato, Paola; Frondini, Francesco; Cassetta, Michele; Pisello, Alessandro; Perugini, Diego (Comptes Rendus. Géoscience)
Experiments were performed at 500 MPa, 1080 °C and water activities (aH$_{2}$O) from 0.0 to 1.0, in fluid-present and fluid-absent conditions, with the aim of constraining the effect of volatiles on phase equilibrium assemblages of a shoshonite from Vulcanello (Aeolian Islands, Italy). Experiments were run both under reducing and oxidizing conditions and results show that proportions, shapes and size of crystals vary as a function of the volatile composition (XH$_{2}$O and XCO$_{2}$) and volatile content. Clinopyroxene (Cpx) is the main crystallising phase and is compositionally analogous to Cpx crystals found in the natural rock. Plagioclase (Pl) is stable only for water activity lower than 0.1, whereas Fe–Ti oxides are present in all experimental runs, except for those where log fO$_{2}$ was lower than ${-}$9, (${Δ }$NNO ${-}$0.11) irrespective of the presence of CO$_{2}$. The addition of CO$_{2}$ (2.8 wt%) in nominally dry experimental charges substantially reduces the crystallinity by ca. 1/3 compared to volatile free experiments. This result has important consequences upon the physical properties of the magma because it influences its viscosity and, as a consequence, velocity during its travel to the Earth surface.Assuming that the widths of Vulcanello conduits vary from 0.5 to 1.5 m, estimates of the ascent velocity vary in the range 1.5 ${× }$ 10$^{-4}$–3.5 ${× }$ 10$^{-2}$ m${· }$s$^{-1}$ for CO$_{2}$ free systems and from 5.7 ${× }$ 10$^{-4}$–1.3 ${× }$ 10$^{-1}$ m${· }$s$^{-1}$ for CO$_{2}$ bearing systems.Since shoshonitic magmas are common not only in the Italian volcanic provinces (Aeolian Arc, Campi Flegrei, Ischia Island, Pontine Islands, Monti Cimini, Monte Amiata, Capraia Island, Radicofani, Roccamonfina) but also in different volcanoes worldwide (Yellowstone, Mariana Arc, Kurile Arc, Tonga Arc, Andean Arc, Kamchatka Arc), we suggest that the new data will be useful to better understand shoshonitic magma behaviour under relevant geological scenarios. As such, we also suggest that hazard evaluation should incorporate the probability of very rapid ascent of poorly-evolved melts from depth.